Research on the technology of noise reduction in hybrid electric vehicle with composite materials. (March 2018) - Liao, Lianying; Zuo, Yanyan; Meng, Haodong; Liao, Xuhui
The noise source of hybrid electric vehicle is varied, which makes the frequency band from low-frequency to high-frequency distribution. Using a single material to control the hybrid electric vehicle interior noise to improve the performance of vehicle, noise, vibration, and harshness performance is limited. In this article, the composite noise reduction materials which have the function of damping and acoustic absorption are used to control the vehicle interior noise. First, the noise characteristics of the hybrid electric vehicle are analyzed. The distribution of the hybrid electric vehicle interior noise is obtained. Then, the sound-absorbing properties of polyester-polypropylene bi-component fiber are analyzed. The low-frequency noise reduction principle of butyl rubber damping material is also analyzed. Finally, the noise reduction materials consisting of polyester-polypropylene and butyl rubber are added to the hybrid electric vehicle roof and floor. After improving material, the hybrid electric vehicle interior noise is test. As the result, the car driver's right ear A-weighting sound pressure levels have been greatly improved. The low-frequency noise below 400 Hz reduced 1.5 dB(A), and the high-frequency noise above 400 Hz reduced 5.2 dB(A). The total noise reduction reached 3.3 dB(A) near the driver's right ear, which significantly improve the noise, vibration, and harshness performance of hybrid electric vehicle.